2013
DOI: 10.5513/jcea01/14.3.1284
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Agroclimatic Factors on Cash Crops Production in Nigeria.

Abstract: This study examined the effects of agroclimatic factors on the yield of cash crops in Nigeria and other variables such as producer prices, exchange rate and level of national income (GDP). The effects of total rainfall, mean temperature, sunshine hour, relative humidity, radiation, exchange rate and GDP on the yields of three cash crops (Cocoa, Palm Kernel and Palm Oil) were estimated for the period 1970-2003 in Nigeria. The methods of analysis employed in the study were mainly error-correction model (ECM) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The study revealed that the variances of parameters of the frontier production function were statistically significant at 1 percent level of significance. The study also revealed that there was positive relationship between farm size, seed, fertilizer, hired labour, family labour and herbicides [16].…”
Section: A Review Of Crop Production In Nigeriamentioning
confidence: 76%
“…The study revealed that the variances of parameters of the frontier production function were statistically significant at 1 percent level of significance. The study also revealed that there was positive relationship between farm size, seed, fertilizer, hired labour, family labour and herbicides [16].…”
Section: A Review Of Crop Production In Nigeriamentioning
confidence: 76%
“…Previous study in Ghana (Amikuzuno and Donkoh, 2012) indicated that variability in rainfall leads to fluctuations in maize yields. Studies in Nigeria (Akinseye et al, 2013;Akintunde, 2013)Kenya (Omoyo et al, 2013) and Pakistan (Ali et al, 2017) similarly indicated that rainfall variability caused severe effect on maize yield. Rice had R 2 value of 0.704, showing 70 % variation in rice yield was associated with climate variability.…”
Section: Climate-crop Yield Relationship In the Basinmentioning
confidence: 98%
“…Therefore, following process is followed to select an appropriate form of empirical model. The existence of panel root in each variable is tested trough Im-Pesaran-Shin test (Akintunde et al, 2013;Amin et al, 2015;Jyoti and Singh, 2020). Statistical results based on this test show that all data series are found stationary.…”
Section: Selection Of An Appropriate Modelmentioning
confidence: 99%
“…Large segments of society are engaged in agriculture sector for their livelihood in larger agrarian economies. Thus, employment and income of the farmers decrease due to decline in agricultural production (Akintunde et al, 2013;Kumar et al, 2016). Climate change, therefore, has a negative impact on livelihood security of the farming community (Jyoti and Singh, 2020).…”
Section: Introductionmentioning
confidence: 99%